Validation of Interactive E-Worksheet Based on a Scientific Approach Assisted by Solar System Scope - Agusta, Fauji; Rahmawati, Annisa Zahra; Nurohman, Sabar (Department of Physics Education, Universitas Mataram, 2024)
The use of e-worksheets is important in 21st-century learning. The purpose of this study is to assess the validity of an interactive e-worksheet based on a scientific approach with the help of Solar System Scope designed for junior high school students and focusing on solar system materials. This is crucially important because a number of challenges students face in grasping the understanding of the abstract scientific concepts, such as the solar system, which is difficult to be understood through normal teaching practices. The way this is being undertaken is through construct validity in which product evaluations are obtained from validators by researchers' developed instruments. This instrument was created using the e-worksheet feasibility indicator as the foundation. The indicators were evaluated and then grouped into five categories. The findings of the study show that the e-worksheet made is very valid. The presentation component has an average validity percentage of 94.42%, the linguistic aspect has an average validity percentage of 90%, the content element has a validity percentage of 93.75%, and the design aspect of e-worksheet also has a validity percentage of 91.67%. This shows that e-worksheet has extraordinary quality in terms of presentation, language, content, and design. The findings of this study can be used to improve the efficiency of the process of acquiring the concept of the solar system in the framework of 21st-century education.